1996
DOI: 10.1128/aac.40.3.715
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chromosomal cephalosporinases produced by Acinetobacter lwoffii and Acinetobacter baumannii clinical isolates

Abstract: The beta-lactamases produced by Acinetobacter lwoffii ULA-501, Acinetobacter baumannii ULA-187, and A. baumannii AC-14 strains were purified and characterized, and their kinetic interactions with several beta-lactam molecules, including substrates and inhibitors, were studied in detail. The three enzymes appeared to be cephalosporinases with different acylation efficiencies (kcat/Km ratio values), and their hydrolytic activities were inhibited by benzylpenicillin, piperacillin, and cefotaxime, which did not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…All of our ribotype A and B isolates possessed a b-lactamase consistent with the chromosomal AmpC enzyme found in A. baumannii [27]. AmpC enzymes may possess weak hydrolytic activity of carbapenems and contribute to resistance in porin-deficient isolates of P. aeruginosa [28].…”
Section: Discussionmentioning
confidence: 95%
“…All of our ribotype A and B isolates possessed a b-lactamase consistent with the chromosomal AmpC enzyme found in A. baumannii [27]. AmpC enzymes may possess weak hydrolytic activity of carbapenems and contribute to resistance in porin-deficient isolates of P. aeruginosa [28].…”
Section: Discussionmentioning
confidence: 95%
“…Intrinsic -lactamase production has been reported in A. baumannii, 10,13 but the present study is the first to report such a high incidence of resistance in A. baumannii.…”
mentioning
confidence: 77%
“…4 Antibiotic susceptibility disks used for the studies were purchased from HiMedia Laboratory (Bombay, India), except for those for aztreonam, imipenem, and moxalactam, which were obtained from Difco (Detroit, MI, USA). The antimicrobial disks used with the concentrations in micrograms in parentheses, were: amikacin (30), ampicillin (30), ampicillin ϩ sulbactam (30), aztreonam (30), carbenicillin (100), cefazoline (30), cefoperazone (75), ceftazidime (30), ceftizoxime (30), ceftriaxone (30), cefuroxime (30), cephaloridine (30), cephotaxime (30), ciprofloxacin (5), cotrimoxazole (25), doxycycline (30), enrofloxacin (10), gentamicin (10), imipenem (10), moxalactam (30), netilmicin (30), ofloxacin (5), piperacillin (100), sparfloxacin (5), sulfasomadine (300), tetracycline (30), triple sulfas (300), ticarcillin (75), and tobramycin (10). Antibiotic susceptibility testing was carried out, as per the directives of the manufacturer and National Committee for Clinical Laboratory Standards (NCCLS) guidelines, 5 on Mueller-Hinton Agar (Difco), using Escherichia coli ATCC 25922 as a quality control strain.…”
mentioning
confidence: 99%
“…Among them, Acinetobacter genomic species 2 (Acinetobacter baumannii or A. baumannii) is the most prevalent species among the clinical specimens (Bouvet and Grimont, 1987;Bergogne-Bérézin and Towner, 1996). Recently, A. baumannii has emerged as an important pathogen causing infections in severely ill patients in intensive care units or immuno-compromised individuals (Bergogne-Bérézin and Towner, 1996;Villegas and Hartstein, 2003) due to its remarkable ability to acquire resistance determinants to various kinds of antimicrobial agents (Perilli et al, 1996). In addition to multi-drug resistance (MDR), it has been found that most of the MDR A. baumannii strains have the ability to form considerable amounts of biofilms (Lee et al, 2008).…”
mentioning
confidence: 99%